2013
DOI: 10.1080/10826068.2013.773342
|View full text |Cite
|
Sign up to set email alerts
|

BIOETHANOL PRODUCTION FROM LEAFY BIOMASS OF MANGO (Mangifera indica) INVOLVING NATURALLY ISOLATED AND RECOMBINANT ENZYMES

Abstract: The present study describes the usage of dried leafy biomass of mango (Mangifera indica) containing 26.3% (w/w) cellulose, 54.4% (w/w) hemicellulose, and 16.9% (w/w) lignin, as a substrate for bioethanol production from Zymomonas mobilis and Candida shehatae. The substrate was subjected to two different pretreatment strategies, namely, wet oxidation and an organosolv process. An ethanol concentration (1.21 g/L) was obtained with Z. mobilis in a shake-flask simultaneous saccharification and fermentation (SSF) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…It was reported that mango leaves contain 26.3% cellulose, 54.4% hemicellulose, and 16.9% lignin . Table depicts the biochemical composition of lignocellulosic feedstocks that have been used in bioethanol production.…”
Section: Prospective Of Secondary Bioethanol Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that mango leaves contain 26.3% cellulose, 54.4% hemicellulose, and 16.9% lignin . Table depicts the biochemical composition of lignocellulosic feedstocks that have been used in bioethanol production.…”
Section: Prospective Of Secondary Bioethanol Productionmentioning
confidence: 99%
“…Mango leaves belong to the group of agricultural lignocellulosic waste with high avaibility especially after pruning session . The prospective of mango leaves in bioethanol production industry is attributed by their elevated holocellulose content . In this article, issues related to the limitations in primary bioethanol production and the prospective of secondary bioethanol will be discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The leafy biomass of mango contributed an ethanol titre of 12.3 g L -1 using naturally isolated cellulase and recombinant enzymes from C. thermocellum [26]. Z. mobilis upon fermentation of 20% (w v -1 ) sugarcane bagasse resulted in an ethanol titre of 6.24 g L -1 and yield of 79% with productivity of 3.04 g L -1 h -1 [27].…”
Section: Ethanol Recovery With Determination Of Purification Process mentioning
confidence: 99%
“…The pretreatment methods are: milling and grinding, pyrolysis, high-energy radiation, high pressure steaming, alkaline (sodium hydroxide) or acid hydrolysis (sulfuric acid), gas treatment (chlorine dioxide, nitrogen dioxide, sulfur dioxide, and ozone), hydrogen peroxide treatment, organic solvent treatment, hydrothermal treatment, steam explosion, wet oxidation and biological treatment, ionic liquids pretreatment. [9,10,11,12,13,14] Alkaline pretreatment is one of the important approaches that has several potential advantages compared to other pretreatment processes, including low operation cost and the reduced degradation of holocellulose and subsequent formation of inhibitors for downstream processing. [15] The main mechanisms of alkaline pretreatment are the degradation of ester bonds and cleavage of glycosidic linkages in the lignocellulosic cell wall matrix, which lead to the alteration of the structure of lignin, the reduction of the lignin-hemicellulose complex, cellulose swelling and partial decrystallization of cellulose.…”
Section: Introductionmentioning
confidence: 99%